Clinical and genetic features of CNGA3 achromatopsia in preschool children: novel insights into retinal architecture and therapeutic window for clinical trials - Lai, Yanting; Hou, Aohan; Zhang, Linyan; Sun, Limei; Yuan, Miner; Ding, Xiaoyan (Frontiers in Medicine, 2025)
PurposeAchromatopsia (ACHM) is a rare genetic disorder with an infantile onset that affects cone photoreceptors. This study aims to provide a comprehensive phenotyping of the retinal structure and identify novel genetic variants in a preschool cohort with ACHM in China.MethodsWe recruited patients with pathogenic genes (CNGA3, CNGB3, GNAT2, PDE6C, PDE6H, and ATF6) known to cause ACHM, all of whom had an age of symptom onset before 6 years of age. Whole exome sequencing, Sanger sequencing, and comprehensive ocular examinations, including optical coherence tomography (OCT), were conducted. Furthermore, retinal outer layer damage was evaluated using a novel modified classification system.ResultsNystagmus (46.13%) and photophobia (46.13%) were the most common initial complaints/reports from parents of our patients. These symptoms are easily noticed early (mean age 0.88 ± 1.07 years at onset of initial symptom). OCT revealed a wide range of degeneration in the outer retina of the fovea, exactly in the interdigitation zone (IZ) and ellipsoid zone (EZ). Retinal outer layer damage was observed in 18 eyes (9 patients), with the modified classification distribution: grade 1 in 1 eye (5.6%), grade 2 in 9 eyes (50.0%), and grade 3 in 8 eyes (44.4%). Eleven novel variants of CNAG3 were identified. The higher grade of outer retinal layer damage was shown in patients with genetic variants, potentially leading to structural changes in the cyclic guanosine monophosphate (cGMP) binding site of the synthesized protein (p = 0.046).ConclusionACHM can manifest at very early stages of life. Mild damage to the outer layers of the retina is a typical change in early-stage ACHM. Patients with genetic variants potentially leading to structural changes in the cGMP binding site of the synthesized protein tend to exhibit more severe retinal phenotypes. Ultimately, our research may aid in formulating guidelines for selecting patients and determining the optimal timing for interventions in upcoming gene replacement therapies.